Implementasi Single Sign-On Menggunakan Protokol Openid Connect (OIDC) Pada Virtual Private Server (VPS) - Sahrin, Muhammad Aditya; Heriansyah, Rudi; Sartika, Dewi (Jurnal Nasional Ilmu Komputer, 2024)
Single Sign-On (SSO) is an authentication method that allows users to access multiple website services using one account and one login process. OpenID Connect (OIDC) is a protocol based on OAuth 2.0 and provides user identity information through JWT (JSON Web Token) tokens. Virtual Private Server (VPS) is a service that can be configured according to user needs. Internet users have many accounts needed to access various online services such as email, social media, online shopping, and many more. Each online service usually has a different username and password. Users often find it difficult to remember each password needed. In addition, using the same password on each online service is also not recommended because it can increase security risks. Based on this problem, an SSO system is needed that is useful for helping users in logging in. The SSO system will be tested with two Dummy Students and Dummy Elearning clients using Black Box Testing with the Equivalence Partitioning technique. From the test results, it was obtained that the SSO system showed that 83% of the test scenarios were successfully carried out